2019
DOI: 10.1016/j.bja.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Side effect profiles of different opioids in the perioperative setting: are they different and can we reduce them?

Abstract: Independent discussion sections for improving inferential reproducibility in published research. Br J Anaesth 2019; 122: 413e20 11. European Medicines Agency. ICH E9 (R1) addendum on estimands and sensitivity analysis in clinical trials to the guideline on statistical principles for clinical trials August 2017.. [Accessed 16 April 2019]. https://www.ema.europa.eu/ en/documents/scientific-guideline/draft-ich-e9-r1addendum-estimands-sensitivity-analysis-clinical-trialsguideline-statistical_en.pdf 12. Tijmstra J.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have confirmed that opioids can safely exert cardioprotective effects both in basic research and in clinical applications [1][2][3][4]. However, the use of opioids is associated with numerous side effects, such as nausea and vomiting, constipation, urinary retention, postoperative ileus, pruritus, respiratory depression and sedation [5]. Additionally, the severity of the side effects is related to the dosage and route of administration.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have confirmed that opioids can safely exert cardioprotective effects both in basic research and in clinical applications [1][2][3][4]. However, the use of opioids is associated with numerous side effects, such as nausea and vomiting, constipation, urinary retention, postoperative ileus, pruritus, respiratory depression and sedation [5]. Additionally, the severity of the side effects is related to the dosage and route of administration.…”
Section: Introductionmentioning
confidence: 95%
“…A number of MOR agonists, such as morphine, have been reported to be effective in alleviating severe pain; however, there were obvious limitations, such as they are prone to abuse, which is associated with an increased, risk of overdose, and serious side effects ( 30 ). In addition, several studies on morphine have shown that it promotes the proliferation, apoptosis, migration, and invasion in the breast ( 22 , 31 ), lung ( 6 , 32 , 33 ) and colorectal cancer cell lines ( 34 ), and a few studies indicated that morphine has an anti-tumor effect ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that reduced opioid consumption may similarly lead to the inhibition of hyperfunction in parathyroid cells and decrease the risk of SHPT recurrence. Meanwhile, with the development of opioid-sparing anesthesia, patients exhibit a better prognosis for multiple surgeries [21,22]. As we know, patients with ESRD usually experience substantial physical, emotional, mental, and psychological impairments that are re ected in the decreased QOL [13,23].…”
Section: Discussionmentioning
confidence: 99%